Pengaruh Transparansi dan Akuntabilitas Pajak terhadap Kepatuhan Wajib Pajak dalam Meningkatkan Tax Ratio - Grace Dame Arta Sinaga; Jisman Lubis; Raysya Hertia; Angelina Grace Bawotong (Akuntansi dan Ekonomi Pajak: Perspektif Global, 2026)
This study examines the effect of tax transparency and accountability on taxpayer compliance and their implications for improving the tax ratio as an indicator of fiscal performance. The research is motivated by the relatively low and fluctuating tax ratio, which reflects tax gaps and structural weaknesses in the taxation system. The study aims to analyze how transparency and accountability influence taxpayer behavior and contribute to strengthening fiscal capacity. A mixed-methods approach was employed, combining descriptive quantitative analysis using secondary data and qualitative conceptual analysis based on the Slippery Slope Framework and the Allingham–Sandmo model. The analytical model positions taxpayer compliance as an intervening variable linking transparency and accountability to the tax ratio. Data were derived from tax ratio trends between 2017 and 2024, including the first quarter of 2025. The findings indicate that tax transparency enhances taxpayer trust by reducing information asymmetry and improving access to fiscal information, while accountability strengthens institutional legitimacy through responsible and auditable financial management. Both variables positively influence voluntary taxpayer compliance, which plays a crucial role in expanding the tax base and increasing government revenue. The study concludes that strengthening transparency and accountability is essential for improving taxpayer compliance, raising the tax ratio, and achieving sustainable fiscal performance.